Evaluation of the surface and the core cultures of adenoids in patients with recurrent adenotonsillitis, obstructive adenoid hypertrophy, and otitis media with effusion - Mehmet Karataş; Sadık Akgün; Sedat Doğan; Mehmet Turğut; Nazif Çalış (National Scientific Medical Center, 2021)
Objective: To determine and to compare the core and the surface bacteriologies of the adenoids of the pediatric patients with obstructive adenoid hypertrophy, recurrent adenotonsillitis, and otitis media with effusion and to evaluate antibiotic susceptibility test patterns of the potential pathogen bacteria. Material and methods: This prospective study was performed on 230 pediatric patients operated for either OAH, RAT, and OME during the time period from April 2014 to July 2017 in the Otorhinolaryngology Clinic of Adıyaman University Education and Research Hospital. Results: The potential pathogen bacteria isolated from the adenoids' surfaces and cores of obstructive adenoid hypertrophy, recurrent adenotonsillitis, and otitis media with effusion groups were as follows: 33/148 (22.3%)-17/148 (11.5%), 9/61 (14.8%)-5/61 (8.2%), and 6/21 (28.6%)-3/21 (14.3%) (p>0.05). Conclusion: There was not statistical difference between the adenoids' surface and core cultures of obstructive adenoid hypertrophy, recurrent adenotonsillitis, and otitis media with effusion.